Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Answer:
We conclude that:
[tex]\frac{18p}{5}+12q+18-\frac{18p}{5}-16q-6=-4q+12[/tex]
Hence, option A is true.
Step-by-step explanation:
Given the expression
[tex]3\left(\frac{6}{5}p+4q+6\right)-2\left(\frac{9}{5}p+8q+3\right)[/tex]
solving the expression
[tex]3\left(\frac{6}{5}p\:+\:4q\:+\:6\right)\:-\:2\left(\frac{9}{5}p\:+\:8q\:+\:3\right)=3\left(\frac{6p}{5}+4q+6\right)-2\left(\frac{9p}{5}+8q+3\right)[/tex]
Expand [tex]3\left(\frac{6p}{5}+4q+6\right)=\frac{18p}{5}+12q+18[/tex]
[tex]=\frac{18p}{5}+12q+18-2\left(\frac{9p}{5}+8q+3\right)[/tex]
Expand [tex]-2\left(\frac{9p}{5}+8q+3\right)=-\frac{18p}{5}-16q-6[/tex]
[tex]=\frac{18p}{5}+12q+18-\frac{18p}{5}-16q-6[/tex]
Group like terms:
[tex]=\frac{18p}{5}-\frac{18p}{5}+12q-16q+18-6[/tex]
Add similar elements: [tex]\frac{18p}{5}-\frac{18p}{5}=0[/tex]
[tex]=12q-16q+18-6[/tex]
Add similar elements: 12q-16q=-4q
[tex]=-4q+18-6[/tex]
[tex]=-4q+12[/tex]
Therefore, we conclude that:
[tex]\frac{18p}{5}+12q+18-\frac{18p}{5}-16q-6=-4q+12[/tex]
Hence, option A is true.
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.